Juniors' voice: Opportunities for ERS 'junior members in 2016. Issue 1 (March 2016) - Boots, Agnes; Flood, Emma; Skoczynski, Szymon
The Junior Members Committee (JMC) is happy to announce another new year of opportunities for European Respiratory Society (ERS) junior members. ERS has significantly evolved and so has the JMC. At the Amsterdam International Congress, new JMC members were elected during assembly meetings. The elections took place in assemblies 1, 6, 8, 9 and 10. Detailed information about new member's activities, along with a contact list, is summarised in table 1. Please use table 1 to guide you on how to get directly involved with junior dedicated ERS activities and your JMC representative. Opportunities for ERS junior members in 2016 http://ow.ly/YC7ME